A Novel Flavone Glycoside: 5,7,3’-trihydroxy-6,4’,5’-Trimethoxyflavone-3’O-α-L-rhamnopyranoside from the Leaves of Mimosa rubicaulis - Yadava, R.N.; Agarwal, P.K.; Kr. Singh, Rajesh (Asian Journal of Chemistry, 2010)
A novel flavone glycoside was isolated from the leaves ofMimosa rubicaulis. Its structure was determined as 5,7,3'-trihydroxy-6,4' ,5'-trimethoxyflavone-3'-O-α-L-rhamnopyranoside byvarious chemical degradations and spectral analysis.